How to Calculate a Partial Nitrogen Mass Budget for Potato - Rishi Prasad; George Hochmuth (EDIS)
This 6-page fact sheet provides information on the importance of nitrogen budgets for potato cultivation and discusses the steps in preparing the budget. It allows growers to understand the inputs, cycling, and exports of nutrients within and away from the farm, develop a nutrient budget, and analyze best management practices (BMPs) for their farm. The results will be increased N fertilizer use efficiency, increased environmental protection, and reduced economic losses associated with potato cultivation. This document will also aid county agents, environmental management advisors, and government agency staff members who help farmers improve and implement nutrient BMPs to protect water quality. Written by Rishi Prasad and George Hochmuth, and published by the UF Department of Soil and Water Science, December 2013.